Command-driven vs. market-oriented environmental regulations: impacts on high-quality development of manufacturing industry - Lin, Chunxin; Wang, Keqiang; Liu, Hongmei (Frontiers in Environmental Science, 2025)
The manufacturing industry is a key area of environmental regulation. However, whether command-driven and market-oriented environmental regulations exert heterogeneous impacts on the high-quality development of the manufacturing industry (HQDM) remains underexplored. This study treats the command-driven low-carbon city pilot policy and the market-oriented carbon emissions trading pilot policy as “quasi-natural experiments”. Firm-level data of listed manufacturing enterprises spanning 2003–2021, it adopts the double machine learning method to evaluate the influence of heterogeneous environmental regulations on the HQDM. The findings show that the low-carbon city pilot policy significantly inhibits the HQDM, whereas the carbon emissions trading pilot policy significantly promotes it. The effect of market-oriented environmental regulation on the HQDM is primarily achieved through the mechanism of technological innovation. In regions where both the low-carbon city pilot policy and the carbon emissions trading pilot policy are implemented, both command-driven and market-oriented regulations boost the HQDM, signifying a synergistic effect between them. Further heterogeneity analysis shows that the results for eastern and western areas, state -owned firms, and technology-intensive manufacturing sectors align with the baseline regression results. The conclusions of this study provide important references for the selection of carbon reduction policies, formulating differentiated emission reduction measures.